ANALISIS OTOT QUADRICEPS FEMORIS TERHADAP FLEKSIBILITAS DAN KONTROL GERAKAN KAKI TAEKWONDO - Bernatdinus Rahmat Telaumbanua; Nada Misva Sebayang; Sandrina Malakiano Naibaho; Revaldo Stevanus sinaga; Mahmudim Matondang; Asep Prima (STKIP Subang, 2025)
This study aims to analyze the influence of the quadriceps femoris muscle on the flexibility and control of leg movements in Taekwondo athletes. The approach used is descriptive quantitative research combined with a review of biomechanics and sports physiology literature. The research subject is a single Taekwondo athlete, Ahmad Jibril (20 years old; height 167 cm; weight 67 kg), who underwent quadriceps strengthening training for two weeks with three main exercise variations: squats, lunges, and vertical leg kicks. Data were collected through knee movement angle measurements using a goniometer and video observation. The results show an increase in flexibility angles from an average of 82.4° to 169.5°, as well as more stable movement control in the ap chagi and dollyo chagi kicks. Literature review supports these findings, indicating that the strength and flexibility of the quadriceps muscles have a positive correlation with the speed and accuracy of kicks. It can be concluded that quadriceps strengthening exercises The quadriceps femoris has a significant effect on improving flexibility and leg movement control in Taekwondo athletes.